Hybrid Learning Model: Its Impact on Mastery of Concepts and Self-Regulation in Newton's Second Law Material - Sulman, Fauzan; Yuliati, Lia; Kusairi, Sentot; Hidayat, Arif (Kasuari: Physics Education Journal (KPEJ), 2022)
This study examines the impact of the Hybrid Learning Model on concept mastery and self-regulation. The research method uses a 2x3 factorial design. After that, data collection used multiple-choice tests for concept mastery and questionnaires for self-regulation. Data analysis using two-way ANOVA with SPSS software. The study results indicate that there is an effect of mastery of concepts using Hybrid Learning and without Hybrid Learning, where the Hybrid Learning model is better than non-Hybrid learning. With students' concept mastery in Newton's Law II material, self-regulation ability is in line and mutually reinforcing. The high concept mastery ability is better than students in the medium and low self-regulation categories. The concept mastery ability in the medium concept mastery category is better than low self-regulation students in the medium concept mastery category. The results also show an influence between the Hybrid learning model and students' self-regulation abilities in the high, medium, and low categories on the ability to understand concepts.